A two-fluid blood stasis model for false lumen thrombosis after type B dissection repair. Issue 13 (3rd October 2022) - Jiang, Xudong; Li, Da; Wu, Peng; Li, Xiaoqiang; Zheng, Tinghui
Abstract: The formation of thrombosis is a major concern in the false lumen (FL) for post-TEVAR (thoracic endovascular aortic repair) patients. Blood stasis is one of the key factors which lead to the formation of thrombosis in the arterial systems. This study proposed a computational model for blood stasis, using a two-fluid principle to track the locations of blood residual over time. The current study applied this novel model to evaluate blood stasis and thrombosis potential in four patient-specific post-TEVAR FLs of type B aortic dissection, with their follow-up in-vivo observations two years after TEVAR. The locations and topologies of residual blood in the FL predicted by the model agreed well with the in-vivo observations of thrombus. In addition, the results corresponded better with clinical observations in terms of interpatient comparison of degree of thrombosis, compared with conventional hemodynamic parameters. The blood stasis model serves as a valuable addition to conventional metrics to better predict thrombosis potential. Collectively, these metrics can provide an efficient non-invasive method for evaluating blood stasis and thrombosis potential in arterial system, and useful guidance for clinicians' operative planning and postoperative evaluation.